Drylot Backgrounding and Finishing Beef - Dhuyvetter, Kevin C.; Tonsor, Glynn T. (My University, 2012)
This publication helps a producer that buys calves and then backgrounds and finishes them, and uses projected input and output prices for illustrative purposes to find the break-even price.
MF593_2012_12
Keywords: MF593; Economics; Livestock; MF